The Role of Transformational Leadership Style, Knowledge, Innovation, Motivation Towards Teacher Performance - Utami , Fidhiya Marlan; Nevi Latina, Nevi Latina; Miko Frenanda, Miko Frenanda; Insyra Nung Fatikha, Insyra Nung Fatikha; M. Fadhil Parhan, M. Fadhil Parhan; Ferdiaz Saudagar, Ferdiaz Saudagar; Muttaqin, Ahmad Sholihin (Indonesian Educational Administration and Leadership Journal (IDEAL), 2024)
This study aims to analyze the role of transformational leadership style on student motivation and learning innovation in schools. Transformational leadership is an approach that focuses on developing individuals, motivating them to reach their full potential. The study involved participants of students from different levels of education in different schools. The research method used was a questionnaire survey given to students to measure their perception of the transformational leadership style demonstrated by the principal. The data were then analyzed using descriptive statistical and regression techniques. The results showed that transformational leadership style has a significant positive influence on student motivation. Principals who are able to motivate students in an inspiring way and attend to their needs and aspirations tend to increase student motivation. In addition, transformational leadership styles also play an important role in enhancing student learning innovation. Principals who encourage students to think creatively, take risks, and find new solutions can encourage innovation in the learning process. The findings have important implications for education practitioners and policymakers. Principals and teachers can use transformational leadership styles as strategies to increase student motivation and learning innovation. In addition, formal education can also pay attention to the importance of developing a transformational leadership style.